Atividade antioxidante e neuroprotetora do ácido alfa lipóico : uma nova perspectiva para o tratamento da doença de Parkinson - Araújo, Dayane Pessoa (2012)
This study aimed to investigate the behavioral and neurochemical effects of α-lipoic acid alone or in combination with LDOPA in an animal model of Parkinson Disease induced by stereotactic injection of the neurotoxin 6-hydroxydopamine (6 -OHDA) in rat striatum. The animals (male Wistar rats, 250-300g) were treated with doses of lipoic acid or 100mg/kg 200mg/Kg alone or in combination with a dose of 50mg/Kg LDOPA 1h before stereotactic injection of 6-OHDA and daily for 14 days after injury. Motor behavior was tested by evaluating apomorphine-induced rotational, horizontal exploratory activity in open field test and asymmetry in the use of the forelegs in the cylinder test. The neurochemical tests were intended to evaluate the antioxidant and neuroprotective effect of α-lipoic acid by determining the lipid peroxidation in the TBARS and determining the concentration of nitrite/nitrate and evaluation of catalase activity. α-Lipoic acid promoted a significant decrease in the number of rotations induced by apomorphine, as well as promoted an improvement in motor performance by increasing the horizontal exploratory activity in open field test and use the paw of the opposite side of the lesion produced by 6-OHDA in the test cylinder. The antioxidant effect of the α-lipoic acid promoted reduction of lipid peroxidation by reducing the TBARS reduced the production of nitrite / nitrate and interacted with the antioxidant system promoting a reduction in endogenous catalase activity. Therefore, α-lipoic acid prevented the damage produced in the dopaminergic neurons by 6-OHDA and the chronic use of LDOPA, indicating that this antioxidant had a neuroprotective effect, being an important therapeutic target for Parkinson disease.